2021
DOI: 10.3390/foods10081884
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Holothuria leucospilota Polysaccharides on Fermentability In Vivo and In Vitro

Abstract: This work aimed to investigate the in-vitro and in-vivo fermentation behaviors of Holothuria leucospilota Polysaccharides (HLP) and the impact on mouse liver antioxidant activity. HLP showed excellent fermentability during in vitro experiments, which was characterized by increased levels of total sugar consumption and short-chain fatty acids (SCFAs). During in vitro fecal fermentation, the fucose contents in the HLP fermentation products (0.174 mg/mL) were higher than those of xylose and galactosamine during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…SCFAs are a series of metabolites of non-starch carbohydrates fermented by the gut microbiota that can provide nutrients for the host and have beneficial effects on the host health [37,38]. In this study, the SCFA contents in feces were determined on day 14 as shown in Figure 5.…”
Section: Scfa Contentmentioning
confidence: 99%
“…SCFAs are a series of metabolites of non-starch carbohydrates fermented by the gut microbiota that can provide nutrients for the host and have beneficial effects on the host health [37,38]. In this study, the SCFA contents in feces were determined on day 14 as shown in Figure 5.…”
Section: Scfa Contentmentioning
confidence: 99%
“…The crude polysaccharides of H. leucospilota were extracted according to the previously published method with slight modification. [ 41 ] The crude polysaccharide of H. leucospilota (200 mg) dissolved in 0.1 m sodium acetate (10 mL) was separated by diethylaminoethyl (DEAE)‐Sepharose Fast Flow and eluted by 1.5 m NaCl–0.1 m sodium acetate solution (column 1.6 cm × 30 cm, pH 5.0). Fractions were passed through a Sephadex G‐100 column (2.5 × 75 cm) and freeze‐dried to obtain HLP.…”
Section: Methodsmentioning
confidence: 99%
“…Published data have suggested that HLP consisted of three main monosaccharides: d ‐glucuronic acid, N ‐acetylgalactosamine, and fucose in the different mole ratios of 0.45:1.00:2.40 (Zhang et al., 2023). HLP have various biological activities, such as antiobesity, antioxidant, antidiabetic, relieving constipation, and immunomodulatory (Wang et al., 2021; Yuan et al., 2019; Zhao et al., 2020). Studies have shown that HLP regulated gut microbiota by fermentation in the gut (Zhang et al., 2023).…”
Section: Introductionmentioning
confidence: 99%